2020
DOI: 10.1038/s41598-020-76141-y
|View full text |Cite
|
Sign up to set email alerts
|

The study of automatic machine learning base on radiomics of non-focus area in the first chest CT of different clinical types of COVID-19 pneumonia

Abstract: To explore the possibility of predicting the clinical types of Corona-Virus-Disease-2019 (COVID-19) pneumonia by analyzing the non-focus area of the lung in the first chest CT image of patients with COVID-19 by using automatic machine learning (Auto-ML). 136 moderate and 83 severe patients were selected from the patients with COVID-19 pneumonia. The clinical and laboratory data were collected for statistical analysis. The texture features of the Non-focus area of the first chest CT of patients with COVID-19 pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…When comparing these two feature categories, it appeared that whole lung features have higher AUCs. A recent study by Tan et al [ 58 ] demonstrated the predictive value of non-focus area of CT images to distinguish different clinical types of COVID-19 pneumonia. In our study, whole lung features provided more relevant characteristics of the disease in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing these two feature categories, it appeared that whole lung features have higher AUCs. A recent study by Tan et al [ 58 ] demonstrated the predictive value of non-focus area of CT images to distinguish different clinical types of COVID-19 pneumonia. In our study, whole lung features provided more relevant characteristics of the disease in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The AI algorithm based on the neural network was established in a number of research articles [ 21 , 22 , 23 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 41 , 42 , 43 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 57 ]. Among the included studies, twenty-nine models were selected for meta-analysis on DL assisted detection for predict COVID-19 [ 21 , 22 , 25 , 26 , 27 , 30 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 46 , 47 , 50 , 51 , 52 , 53 , 54 , 56 , 57 ] and fourteen models on ML assisted detection for predict COVID-19 [ 21 , 24 , 28 , 31 , 38 , 43 , 45 , 46 , 48 , 49 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 37 studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] of image-based analysis, the pooled sensitivity was 0.90 (95% CI, 0.90 - 0.91), specificity was 0.90 (95% CI, 0.90 - 0.91), the AUC was 0.96 (95% CI, 0.91 - 0.98), and diagnostic odds ratio (DOR) was 88.98 (95% CI, 56.38 – 140.44) as shown in ( Figure 2 ) ( Supplementary Figures 2-8 ).
Figure 2 The summary receiver-operating characteristic (SROC) curves of the diagnostic performance of AI and CT-Scan on detection.
…”
Section: Diagnostic Test Accuracy (Dta)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a radiomic model was demonstrated to predict the tumor invasiveness of pulmonary adenocarcinomas appearing as ground-glass nodules (18,21). Radiomics-based models were recently proposed to improve the diagnosis of COVID-19 on chest CT images (22)(23)(24). To the best of our knowledge, no studies investigated the possibility of discriminating the GGOs due to COVID-19 pneumonia from those due to non-COVID-19 acute lung disease.…”
Section: Introductionmentioning
confidence: 99%